2018
DOI: 10.1038/s41467-018-06071-x
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal toroidal diamond anvils for high pressure experiments beyond 5 megabar

Abstract: Static compression experiments over 4 Mbar are rare, yet critical for developing accurate fundamental physics and chemistry models, relevant to a range of topics including modeling planetary interiors. Here we show that focused ion beam crafted toroidal single-crystal diamond anvils with ~9.0 μm culets are capable of producing pressures over 5 Mbar. The toroidal surface prevents gasket outflow and provides a means to stabilize the central culet. We have reached a maximum pressure of ~6.15 Mbar using Re as in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 26 publications
6
53
1
Order By: Relevance
“…The future in DAC foresees many more developments, mainly on two fronts: I) focus ion beam techniques will play a fundamental role in DAC, permitting to sculpt futuristic microanvils (<20 µm) which will extend the range of pressure well above the 400 GPa, the ceiling pressure for one-stage DAC. Recently, micromilling gem-quality diamond tips shaped in toroidal form have been shown to greatly extend the accessible pressure up to ∼ 550 to 600 GPa on DACs [117,118,119]. II) thanks to the advancements on characterization techniques such as new X-ray sources in synchrotron and X-ray free electron lasers, producing much brighter, subµ-beams will enable the study of compression volumes of only tenths of picolitres [116].…”
Section: Diamond Anvilsmentioning
confidence: 99%
“…The future in DAC foresees many more developments, mainly on two fronts: I) focus ion beam techniques will play a fundamental role in DAC, permitting to sculpt futuristic microanvils (<20 µm) which will extend the range of pressure well above the 400 GPa, the ceiling pressure for one-stage DAC. Recently, micromilling gem-quality diamond tips shaped in toroidal form have been shown to greatly extend the accessible pressure up to ∼ 550 to 600 GPa on DACs [117,118,119]. II) thanks to the advancements on characterization techniques such as new X-ray sources in synchrotron and X-ray free electron lasers, producing much brighter, subµ-beams will enable the study of compression volumes of only tenths of picolitres [116].…”
Section: Diamond Anvilsmentioning
confidence: 99%
“…Thus, they can be expressed by two parallel crystal planes (hkl)a//(h 0 k 0 l 0 )b and two parallel directions [uvw]a and [u 0 v 0 w 0 ]b, where [uvw] and [u 0 v 0 w 0 ] lie in the (hkl) and (h 0 k 0 l 0 ) planes. Wheeler and Lewis 20 found that the shock-quenched diamond contains both CD and HD domains with orientations of (100)gr//(11-1)cd + [010]gr// [1][2][3][4][5][6][7][8][9][10]cd and (100)gr//(001)hd + [010]gr//[010]hd, respectively. They proposed that the phase transition can be achieved by the displacement of adjacent pairs of <À120> row with relative shears on alternating graphite basal planes.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…[1][2][3] Due to its many remarkable properties, diamond is in great demand in both industry and fundamental research. [4][5][6][7] However, at ambient conditions graphite is more stable than diamond (with a difference of $10 meV/atom from the modern quantum mechanical simulation based on density functional theory [DFT] 8 and $17 meV/atom from more accurate diffusion Monte Carlo calculation 9 ). Despite years of efforts, synthesizing diamond from graphite was not possible until the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of these reactions is also of a primary interest for the development of the methodology of ultra‐high pressure high temperature experiments, in which Re gaskets are commonly used. The range of currently achievable static pressures has been extended to ≈ 1000 GPa due to implementation of double‐stage diamond anvil cells (dsDAC) and to ≈ 600 GPa with toroidal type anvils (tDAC) . In order to achieve such extreme pressures, the linear size of samples and sample chambers should be drastically decreased.…”
mentioning
confidence: 99%